Applying Small Group Discussion to Improve Students' Reading Comprehension at The First Grade of SMP PGRI KLIS - Ririwelas, Natalie; Anaktototy, Karolis (Koli Journal : English Language Education, 2023)
This research was aimed at improved reading skill among students at SMP PGRI Klis. This Classroom Action Research was conducted in two cycles where all the data have been collected through test and the questionnaire. Based on the data, it was found that (1) narrative text as a teaching media can help the students to better understand English reading texts. From 19 students, 5 students or 76, 66 of % the students achieved the indicator of success; (2) the use of narrative text or some media in implementing using narrative text as a teaching media to improve students reading comprehension in order to stimulate the students to learn English reading comprehension that can be seen by students’ responses among 19 students, 10 students were interested to learn English reading comprehension through using narrative text and (3) the using narrative text as a teaching media can increase students’ reading comprehension. This result indicated that the using narrative text as a teaching media has successfully applied in increasing students’ reading comprehension.